Internalisasi Nilai-Nilai Karakter Pada Pembelajaran Praktikum Virtual Fisika dalam Konteks Kurikulum 2013 di MAN Insan Cendekia Jambi : Internalization of Character Values in Physics Virtual Practicum Learning in the 2013 Curriculum Context at MAN Insan Cendekia Jambi - Gunawan Gunawan; Maison Maison; Jefri Marzal (Universitas Jambi, 2022)
The 2013 curriculum emphasizes character in every learning. One effort to shape students' character of discipline, honesty, curiosity, independence, and responsibility is the internalization of character values ​​in the learning of Physics Practicum. This study aims to describe the internalization of the character values ​​of students at MAN Insan Cendikia Jambi. The method used in this research is a descriptive qualitative method through observation, self-assessment, and interviews of six students of class XI consisting of three female students (S1W, S2W, and S3W) and three male students (S4L, S5L, and S6L). The results showed that the six students experienced internalization of character values ​​by accepting and carrying out the practicum. Moreover, students with high disciplinary characters also had high responsibility characters, while students with low disciplinary characters also had low responsibility characters.